Session Topic: Finance and Industrial Organization: Discussion - Long, John B. (Journal of Finance, 1976)
John B. Long, Jr., Session Topic: Finance and Industrial Organization: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 740-743